B2.5-Eirene modeling of radial transport in the MAGPIE linear plasma device. (23rd March 2017) - Owen, L W; Caneses, J F; Canik, J; Lore, J D; Corr, C; Blackwell, B; Bonnin, X; Rapp, J
Abstract: Radial transport in helicon heated hydrogen plasmas in the MAGnetized Plasma Interaction Experiment (MAGPIE) is studied with the B2.5-Eirene (SOLPS5.0) code. Radial distributions of plasma density, temperature and ambipolar potential are computed for several magnetic field configurations and compared to double Langmuir probe measurements. Evidence for an unmagnetized ion population is seen in the requirement for a convective pinch term in the continuity equation in order to fit the centrally peaked density profile data. The measured slightly hollow electron temperature profiles are reproduced with combinations of on-axis and edge heating which can be interpreted as helicon and Trivelpiece–Gould wave absorption, respectively. Pressure gradient driven radial charged particle diffusion is chosen to describe the diffusive particle flux since the hollowness of the temperature profiles assists the establishment of on-axis density peaking.